PENGEMBANGAN MODEL PENILAIAN KINERJA PEMBELAJARAN KETERAMPILAN BERBICARA - Subhan, Roni (Balai Besar Guru Penggerak Jawa Timur, 2023)
The aim of this research is to develop a teaching and learning assessment model for speaking skills in Grade VII of MTs. Negeri, Sumberbaru, Jember. The research method used in this study is Research and Development, following Brog and Gall's research model. The subjects of the study were 26 students in Grade VII at MTs. Negeri Sumberbaru, Jember. The research findings are as follows: Firstly, based on the content expert's assessment of the performance assessment, 68.81% of the assessment items obtained a score of 3, while the remaining 32.19% obtained scores below 3. Therefore, it can be concluded that this assessment can be implemented for 35.45% of the items. The performance assessment guide received a score of 4, with 64.55% of the items obtaining a score of 3. Based on the teacher's evaluation, out of the 22 assessment items in the performance assessment guide, approximately 12.12% received a score of 4, 54.55% received a score of 3, and 33.33% received a score of 2. No one chose a score of 1. In the field evaluation, approximately 81.28% of the students responded positively to the performance assessment guide items. Approximately 10.76% of the responses indicated a lack of agreement, with around 3 answers out of 20 questions. Approximately 7.96% of the students disagreed with the assessment model. These findings indicate that students have a positive response to the applied evaluation model. AbstrakTujuan penelitian ini adalah untuk mengembangkan model penilaian pengajaran dan pembelajaran keterampilan berbicara di kelas VII MTs. Negeri, Sumberbaru, Jember. Metode penelitian ini menggunakan penelitian Research and Development dengan model penelitian Brog and Gall. Subjek yang digunakan adalah siswa kelas VII berjumlah 26 siswa di sekolah MTs. Negeri Sumberbaru, Jember. Hasil penelitian didapatkan sebagai berikut. Pertama, berdasarkan penilaian ahli konten terhadap kinerja penilaian yang mendapatkan skor 3 adalah 68,81%, sisanya mendapatkan skor 32,19%, sehingga dapat disimpulkan bahwa penilaian ini dapat diterapkan sebesar 35,45% item, panduan penilaian kinerja mendapatkan skor 4, yang mendapatkan skor 3 adalah 64,55%. Berdasarkan tes guru, dari 22 item penilaian untuk panduan penilaian kinerja 12,12 %, item panduan penilaian kinerja mendapat skor 4. Sedangkan yang memilih skor 3 adalah 54,55 %, sedangkan yang memilih skor 2 mencapai 33,33%. Untuk skor 1 tidak ada yang memilih. Evaluasi Lapangan, Dari item penilaian untuk panduan penilaian kinerja 81,28% siswa yang merespon dengan pernyataan setuju. Sedangkan yang kurang setuju sekitar 3 jawaban dari 20 nomer pertanyaan atau sekitar 10,76% sedangkan siswa yang tidak setuju sekitar 7,96%. Dengan demikian instrumen keterampilan berbicara memenuhi kriteria kevalidan dan kepraktisan.